Female Leadership Portraits in Commercial Movies: Gender Social Representations from the STEAM Sector - Buelvas-Baldiris, Tatiana; Rubira-García, Rainer (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
To encourage girls and women to pursue STEAM careers, it is crucial to increase the positive representation of female role models in science. The study uses the Bechdel test and an adapted Greimas Actantial Method to analyse mainstream films. Results show that female characters are often attractive, Caucasian scientists, not mothers, and play secondary roles above all. The most represented careers were in Biology, Astronomy, and Social or Human Behavioural Sciences. Representation of women in leadership positions in the STEAM sector in commercial movies is clearly deficient.